Finite Element Analysis of Disc Insulator Type and Corona Ring Effect on Electric Field Distribution over 230-kV Insulator Strings - Akbari, Ebrahim; Mirzaie, Mohammad; Rahimnejad, Abolfazl; Asadpoor, Mohammad Bagher (International Journal of Engineering and Technology, 2012)
Insulator strings are widely used in power systems for the dual task of mechanically supporting and electrically isolating the live phase conductors from the support tower. However, the electric field and voltage distribution of insulator string is uneven which may easily lead to corona, insulators’ surface deterioration and even flashover. So the calculation of the electric field and voltage distribution along them is a very important factor in the operation time. Besides, despite the variety of insulator material and profiles, no remarkable endeavor regarding their impacts upon electric field distribution has been made so far. In this paper, three-dimensional Finite Element Method (3-D FEM) software–Maxwell is employed to simulate several 230-kV insulator strings with various types of porcelain and glass disc insulators and the electric field along them were compared, to investigate the effect of insulator types on electric field distribution.